Handbook of Quality of Life in African Societies - Eloff, Irma (International Handbooks of Quality-of-Life, 2019)
This handbook reflects on quality-of-life in societies on the continent of Africa. It provides a widely interdisciplinary text with insights on quality-of-life from a variety of scientific perspectives. The handbook is structured into sections covering themes of social context, culture and community; the environment and technology; health; education; and family. It is aimed at scholars who are working towards sustainable development at the intersections of multiple scientific fields and it provides measures of both objective and subjective quality-of-life. The scholarly contributions in the text are based on original research and it spans fields of research such as cultures of positivity, wellbeing, literacy and multilinguism, digital and mobile technologies, economic growth, food and nutrition, health promotion, community development, teacher education and family life. Some chapters take a broad approach and report on research findings involving thousands, and in one case millions, ofparticipants. Other chapters zoom in and illustrate the importance of specificity in quality-of-life studies. Collectively, the handbook illuminates the particularity of quality-of-life in Africa, the unique contextual challenges and the resourcefulness with which challenges are being mediated. This handbook provides empirically grounded conceptualizations about life in Africa that also encapsulate the dynamic, ingenious ways in which we, as Africans, enhance our quality-of-life. .